Distribution Characteristics and Ecological Risk Assessment of Heavy Metals in Typical Soil Profiles of Muchuan County, Sichuan Province - Bixia LIAO; Wenling SHEN; Ling HE (Yankuang ceshi)
BACKGROUNDSoil is a precious resource for human survival and social development. The quality of the soil environment is impacted by a variety of issues due to the social economy’s rapid expansion, and the issue of heavy metal contamination in farmed land has garnered great attention globally. Heavy metals in soil pose a severe risk to the security of agricultural products and public health due to their persistence, latency, and ease of entry into the food chain.　　In recent years, many scholars have carried out research on soil heavy metal pollution and ecological risk assessment under different conditions such as natural conditions, industrial and mining industries and developed transportation in different regions. Zhou et al.[11] found that Xiong’an New Area was affected by the production activities of surrounding enterprises. The contents of As, Cd, Cu, Pb and Zn in some root soil samples exceeded the screening value standard for soil pollution risk of agricultural land (GB 15618—2018), and the exceeding ratios were 23.33%, 96.67%, 33.33%, 33.33% and 10.00%, respectively. Song et al.[12] evaluated the characteristics of heavy metal pollution in the surface soil of Fuping County, Hebei Province, and found that As and Cd exceeded the acceptable carcinogenic risk level (As is 10−5, Cd is 10−6). Kumar et al.[10] collected data on heavy metal-contaminated soils in India from 1991 to 2018. The average Cd content of all soil types exceeded the limit values, and the potential ecological risk values of Cd were greater than 320, reflecting a higher ecological risk. For the heavily polluted soil, according to the different pollution situation in our country, the remediation measures are taken according to local conditions. However, due to the wide area of contaminated soil and the complex composition of pollution sources, the current soil remediation work still faces huge problems.OBJECTIVESTo study the vertical distribution characteristics of heavy metals in soil, the relationship between soil heavy metals and soil nutrient elements, as well as the degree of pollution and potential ecological risks.METHODSThe contents of Cd, Cu, Ni, Pb, Zn were measured using inductively coupled plasma-mass spectrometry (ICP-MS); As content was determined by hydride generation atomic fluorescence spectrometry (HG-AFS); P and K2O contents were determined by X-ray fluorescence spectrometry (XRF); N content was determined by oxidation combustion gas chromatography (GC); Hg content was determined by cold vapor atomic fluorescence spectrometry (CV-AFS); Organic carbon content was determined by high-frequency combustion infrared absorption method (IR); potentiometric method (POT) was used to measure soil pH value. Statistical analysis and calculation of soil heavy metal content, pollution index, and ecological risk index were conducted using Excel 2016. Pearson correlation analysis was conducted using SPSS 26, and the degree of soil heavy metal pollution was evaluated using the geoaccumulation index (Igeo). Potential ecological risk index (RI) values were selected to evaluate potential ecological risks.RESULTSThe average contents of As, Cd, Cu, Hg, Ni, Pb, and Zn in the soil of YS plot were 20.8mg/kg, 0.35mg/kg, 26.38mg/kg, 0.121mg/kg, 33.29mg/kg, 42.37mg/kg, and 94.47mg/kg, respectively; The average contents of As, Cd, Cu, Hg, Ni, Pb, and Zn in the soil of PS plot were 7.21mg/kg, 0.32mg/kg, 28.32mg/kg, 0.028mg/kg, 47.34mg/kg, 33.29mg/kg, and 116.45mg/kg, respectively; The average contents of As, Cd, Cu, Hg, Ni, Pb, and Zn in the soil of GS plot were 5.42mg/kg, 0.16mg/kg, 22.38mg/kg, 0.08mg/kg, 31.8mg/kg, 30mg/kg, and 75.03mg/kg, respectively. The concentrations of As, Cd, Hg, Ni, Pb, and Zn were higher than the national and Sichuan soil background values, indicating that these metals were relatively enriched in the soil of Muchuan County. The relationship between seven heavy metals at different soil depths was evaluated through Pearson correlation analysis (seen in Table 4). There was a significant positive correlation between heavy metals, indicating their widespread homology. In the PS profile, the correlation between Cd, Hg and organic carbon was very high, with correlation coefficients of 0.934 and 0.955, respectively (Fig.5); As, Cd, Cu, Hg, Zn showed a highly significant negative correlation with pH, and the correlation between Cd, Hg content and soil pH was shown in Fig.5, with correlation coefficients of −0.964 and −0.944, respectively. The content of heavy metals in soil was closely related to organic carbon and pH value, which should be attributed to the adsorption of organic matter and the fact that pH not only affected the electrostatic adsorption of heavy metals by soil particles, but also damaged the inert part of the parent material. Soil organic matter and pH value are important factors affecting the migration of heavy metals in soil. The surface soil had a high content of organic matter, multiple adsorption sites, and a high soil pH value, which reduced the solubility of heavy metals and thus the metal migration rate.　　Soil pollution assessment results. The Igeo values of Cu and Zn in all soil profiles were less than 0, indicating that the soil in the study area was not contaminated by these heavy metals. The Igeo value of Cd at four depths was significantly reduced. Except that the Igeo value at GS point was less than 1, YS and PS were greater than 1, indicating that the Cd pollution degree of corn land (YS, PS) was more serious than that of tea garden land (GS). This may be due to the difference of tillage conditions, and the Igeo value of surface soil at YS point was between 2 and 3, showing moderate-strong pollution. The Igeo values of As, Hg, Ni and Pb at four depths were all less than 1 and close to 0, indicating that the soil pollution was slight, which may be caused by human input or natural changes. In general, conventional agricultural practices lead to the enrichment of heavy metals in soils due to excessive use of fertilizers and pesticides, wastewater irrigation and atmospheric deposition. Zhao et al.[42] found that use of fertilizers and manure increased the content of heavy metals (Cd, Cu, Pb, and Zn) by approximately 3% per year. The order of heavy metal pollution degree from high to low is Cd>Hg>As>Pb>Ni.　　Potential ecological risk assessment. According to the description of risk level, the YS plot had the highest potential risk index for Cd and Hg, and there was a significant ecological risk of Cd and Hg at depths of 0-140cm (80≤Ei<160), among which the surface soil Cd had a strong ecological risk (160≤Ei<320). It indicates that Cd pollution sources in the region may be affected by past agricultural activities, including fertilizers and pesticides. The soil Cd of PS plot exhibited strong ecological hazards (160≤Ei<320) at the depth of 0-30cm while exhibiting strong ecological hazards (80≤Ei<160) at 60-110cm. The Cd and Hg in surface soil at the GS plot site had moderate ecological risks (40≤Ei<80). The value of RI showed a strong ecological risk (300≤RI<600) at 0-10cm of the YS plot, and a moderate ecological risk (150≤RI<300) at 30-140cm. Moderate ecological hazards (150≤RI<300) were present in the PS plot, while mild ecological hazards (RI<150) were present at 60-110cm. The ecological hazards of GS plot at 0-130cm were relatively weak. The Ei values of heavy metals in soil decreased with the increase of depth, which was consistent with the evaluation results of Igeo pollution. The Ei values of Cd in the three profiles were relatively high, indicating that special attention should be paid to the control of heavy metal pollution.CONCLUSIONSAccording to the results of soil vertical profile data, it can be concluded that heavy metal content tends to accumulate in the surface soil, and its content decreases with increasing depth. The Igeo value and Ei value also decrease with the increase of formation depth. The geoaccumulation index and potential ecological risk analysis indicate that Cd poses significant ecological risks to the local soil, and appropriate measures should be taken to strengthen pollution prevention and control in the area to avoid harm to human health. The content of heavy metals is closely related to soil nutrients and physicochemical properties, positively correlated with organic carbon content, and negatively correlated with pH value. According to the research results, it is suggested to carry out further research on the accumulation of heavy metals in soil, rationally assess its ecological harm, and ensure the safe use of land.